A Response to the Commentary Entitled: “Addressing the Shortage of Health Professionals in Rural China: Issues and Progress” - Qian Yang; Hengjin Dong (International Journal of Health Policy and Management, 2015)
The principal problems of healthcare services in China are “difficulty in seeing a doctor”and “high expense of getting medical service” (commonly known in Chinese as “kan bing nan, kan bing gui”). The central Chinese government has already launched the bottom-up cascading medical system and two-way referral system recently in order to solve these problems (1). Only when patients go to medical institutions in an orderly fashion, can we see the hope of breaking the kan bing nan, kan bing gui (2). However, we face a number of obstacles when implementing the referral policies. The biggest obstacle is the lack of Human Resource (HR) for primary care both in capacity and volume (3). The central Chinese government has launched a series of policies to deal with the shortage of HRs in rural areas. Profound measurements involve postgraduate training for General Practitioner (GP) (a three-year plan beginning in 2010 for producing health professionals for rural areas and improving rural retention), “3+2” medical education model (3-year diploma education and 2-year postgraduate GP training), and in-service training for physicians in rural areas (4). It is not the time to assess their effectiveness, however, these measurements are certain to improve the capacity of Community Health Service (CHS) institutions.